Avaliação da dor em vítimas de traumatismo cranioencefálico criticamente enfermas - Ribeiro, Caíque Jordan Nunes (2016)
Background: pain assessment in noncommunicative critical patients is challenging for the health care teams, especially in traumatic brain injury victims. Although behavioral scales are considered appropriate and consistent, there are few studies involving this population. Objectives: to evaluate the pain management in in critically ill victims of traumatic brain injury. Method: this is an observational, prospective, and analytical study, developed at clinical and surgical intensive care units of a general, public and high complexity hospital in Aracaju, Sergipe, Brazil. The sample was non-probabilistic of convenience, consisting of 37 victims of moderate to severe traumatic brain injury, sedated and mechanically ventilated. We collected demographic, clinical, trauma-related, sedation-related and prescribed analgesia-related data. Ramsay and Richmond Agitation Sedation Scale (RASS) scores were used to assess sedation depth. Pain was evaluated using the Behavioral Pain Scale - Brazilian version by two independent observers, simultaneously and without communication between them. The study was approved by the Ethics Committee of the Federal University of Sergipe (CAAE: 38567714.1.0000.5546). Categorical variables were expressed as absolute and relative frequencies. Quantitative variables were represented as mean ± standard deviation or standard error of mean. Inferential analysis was performed using nonparametric tests (discriminant validity), agreement tests (intraclass correlation coefficients and Cohen's kappa) and Pearson correlation tests. The internal consistency of scale was estimated by α-Cronbach's coefficient. P-values < 0.05 were considered significant. Results: participants were predominantly male (91.0%), working age adults (37.7 ± 13.1), non-white (67.6%), with low education (4.6 ± 3.9 ), countryside residents (73.0%) and wihtout previous diseases (97.3%). Severe head trauma was prevalent (91.9%), caused by motor vehicle collisions (89.1%) and more than two-thirds did not use the safety device. Fentanyl and Midazolam were the drugs most used for sedation and analgesia. Deep sedation (Ramsay = 5.5 ± 0.8; RASS = -3.7 ± 1.7) was significantly correlated with the BPS scores (p ≤ 0.005). During endotracheal suctioning, physiological parameters and BPS scores rose substantially (p <0.001), but without statistical association. Satisfactory results of agreement percentages (59.4% to 100%), effect size (0.8 to 1.3) and internal consistency (0,7≤α≤0,9) were found. Conclusion: pain was present during endotracheal suctioning and the BPS - Brazilian version proved to be a valuable, reliable and consistent tool to assess pain in traumatic brain injury victims.